Fluorescence In Situ Imaging of Dendritic RNAs at Single‐Molecule Resolution. Issue 1 (15th July 2019) - Batish, Mona; Tyagi, Sanjay
Abstract: RNA localization is an important step in gene regulation. Imaging RNAs in fixed and live cells provides contextual information about RNA distribution in the cells. Here, we provide detailed protocols for performing single‐molecule fluorescence in situ hybridization (smFISH). smFISH detects mRNA molecules at single‐molecule resolution in fixed neuronal cells using ∼50 small oligonucleotide probes for each mRNA. The technique has been successfully applied to understand RNA localization and distribution in various biological systems, ranging from Drosophila to the mammalian nervous system. The probes are small enough to bind to structured RNAs or RNAs that are part of RNA‐protein complexes, thereby accounting for ∼85% of the total RNA; this enables a level of sensitivity equivalent to that of quantitative real‐time PCR, but with anatomical resolution. © 2019 by John Wiley & Sons, Inc.